PERENCANAAN JUMLAH TOLL GATE - Muhammad Zainul Arifin; Devina Candra Puspita Rini; Khairul Arifin; Ludfi Djakfar (Rekayasa Sipil, 2021)
Pasuruan-Probolinggo toll road was built to increase economic sector in East Java Region. Prior to construction, it’s necessary to analyze potential of toll road users and planning the ideal number of toll gates to comply with minimum service standards. This study uses Stated Preference method to determine vehicle switch, planning of ideal toll gates using Poisson Distribution, and FIFO queuing model used to analyze toll gate service system. Based on analysis, the largest potential road users who will switch to use Pasuruan-Probolinggo toll road section IV in 2021, 2025, 2030, 2035, and 2040 are 5,49%, 23,84%, 30,63%, 30,63%, and 30,63%. The calculation of toll gates is adjusted to the calculation of potential toll road users in 2025, 2030, 2035, and 2040 with the arrival of 385, 503, 657, and 858 vehicles/hour/strip. So, the ideal number of toll gates needed in 2025-2030, are 4 units, and 2035-2040 are 8 units of toll gates.